Is the 'hate' in hate speech the 'hate' in hate crime? Waldron and Dworkin on political legitimacy. (3rd April 2019) - Gould, Rebecca Ruth
ABSTRACT: Among the most persuasive arguments against hate speech bans was made by Ronald Dworkin, who warned of the threat to political legitimacy posed by laws that deny those subject to them adequate opportunity for dissent. In his influential defence of hate speech bans, Jeremy Waldron addresses these objections. Dworkin's concern with political legitimacy is misplaced, he argues, given the provision speech bans make for substituting permissible modes of expression for impermissible ones. I argue that this defence of speech bans misidentifies the 'hate' in hate speech with the 'hate' in hate crime. In contesting Dworkin, Waldron fails to contend with the necessarily entangled criminalisation of manner and viewpoint entailed in hate speech bans. By failing to grapple with the way in which every linguistic sign is constituted by both manner and viewpoint, Waldron sidesteps the ways in which hate speech bans undermine political legitimacy within liberal democracies.